Seven ways to get a grip on running a successful promotions process - Field, Simon (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Promotion within an academic institution is often a key component of a career; however, there are often barriers to successful applications. A streamlined and transparent process can assist faculty members in their goals of obtaining promotion, leading to greater security and satisfaction. This paper describes a methodology designed at a local level to maximize opportunities for success, in the hope that others may learn from the experience and advocate for similar changes within their own institutions.